2019
DOI: 10.2478/bile-2019-0013
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modeling of the Coinfection Dynamics of Malaria-Toxoplasmosis in the Tropics

Abstract: Coinfection by Plasmodium species and Toxoplasma gondii in humans is widespread, with its endemic impact mostly felt in the tropics. A mathematical model is formulated as a first-order nonlinear system of ordinary differential equations to describe the coinfection dynamics of malariatoxoplasmosis in the mainly human and feline susceptible host population in tropical regions. Comprehensive mathematical techniques are applied to show that the model system is bounded, positive and realistic in an epidemiological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Ogunmiloro [2] considered a mathematical model of malaria-toxoplasmosis co-infection dynamics. The analysis shows that the model is locally and globally stable, sensitivity analysis revealed that the spread malaria-toxoplasmosis can be achieved via the availability of treated bed nets, proper environmental sanitation, availability of drugs etc.…”
Section: Original Research Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Ogunmiloro [2] considered a mathematical model of malaria-toxoplasmosis co-infection dynamics. The analysis shows that the model is locally and globally stable, sensitivity analysis revealed that the spread malaria-toxoplasmosis can be achieved via the availability of treated bed nets, proper environmental sanitation, availability of drugs etc.…”
Section: Original Research Articlementioning
confidence: 99%
“…Malaria is an infectious disease caused by Plasmodium parasite, spread through the bites of an infected female Anopheles mosquito [1,2]. According to the World Health Organization (WHO), the estimated…”
Section: Introductionmentioning
confidence: 99%
“…Three regional conditions were obtained through this analysis, showing the dynamics of the toxoplasmosis epidemic of these two important parameters with each interpretation of the bifurcation region. The widespread of co-infection by Plasmodium species and Toxoplasma gondii in humans mostly in the tropical region motivated Ogunmiloro to study the co-infection dynamics of malaria-toxoplasmosis in the mainly human and feline susceptible host population in [18]. The analysis showed that malaria-toxoplasmosis infection free equilibrium is locally and globally stable if the basic reproduction number is less than unity.…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, Song et al introduced a malaria-dynamics mathematical model [9]. In turn, Ogunmiloro presented a model to simulate the infectivity of plasmodium and toxoplasma [10]; Koutou et al proposed an ELPA model to study the relationship of malaria with mosquito population [11]; and Bakary et al suggested a model to analyze the impact of frequent biting of mosquitoes and blood transfusions [12].…”
Section: Introductionmentioning
confidence: 99%